The effects of a ‘study abroad’ programme on the development of verb morphology for the expression of past time by the advanced learner: a lexical approach - Martin Howard (Teanga: The Journal of the Irish Association for Applied Linguistics, 2020)
This article presents an investigation of the benefits of a period of residence in a francophone country for a group of Irish university learners of French in relation to their acquisition of verb morphology to express past time. The study makes a cross-sectional comparison between this group of learners with two other groups: one, a group of learners before they leave for a period of residence abroad, and the other consisting of learners who chose not to partake in such a programme, but who continued to have further access to the target language through classroom instruction. Whilst results suggest that ‘study abroad’ has a more important effect than instruction, as manifested by general increases in the frequency, as well as accuracy, of use of the past tenses; the increased range of lexical verbs marked for past time; and a reduction in formal error; there remain a number of lexical limitations on such marking, such that past time marking continues to be constrained by the lexical value of the verb. In particular, unlike the passé composé, the imparfait is used with a limited range of verbs, notably étre and avoir. The occurrence of verbs conjugated in both tenses also remains limited, whereby the learners tend not to alternate freely between both past time forms with individual lexical verbs, but rather to restrict individual lexical verbs to a single past time form.